Comparison of Abdominal Aortic Aneurysm Sac and Neck Wall Motion with 4D Ultrasound Imaging. (October 2020) - Derwich, Wojciech; Wittek, Andreas; Hegner, Achim; Fritzen, Claus-Peter; Blase, Christopher; Schmitz-Rixen, Thomas
Abstract : Objective: The rupture of abdominal aortic aneurysms (AAAs) is associated with high mortality despite surgical developments. The determination of aneurysm diameter allows for follow up of aneurysm growth but fails in precisely predicting aneurysm rupture. In this study, time resolved three dimensional ultrasound (4D ultrasound) based wall motion indices (WMIs) are investigated to see if they are capable of distinguishing between uneven affected regions of the aneurysm wall. Methods: In a prospective study, 56 patients with an AAA were examined using 4D ultrasound. Local longitudinal, circumferential, and shear strains were computed using custom methods. The deformation of the neck and sac of each aneurysm was characterised by statistical indices of the obtained distributions of local wall strains (WMIs): mean and peak strain, heterogeneity index, and local strain ratio. The locations of regions with highest local peak strain were determined. Results: Compared with the aneurysm neck, the sac is characterised by low mean strain, but highly heterogeneous deformation, described by high local strain ratio and heterogeneity index. Differences were highly significant ( p  < .001) for all strain components. The regions with the highest circumferential peak strain were found more often in the posterior part of the aneurysm neck ( p  < .050) and sac ( p  < .001) regions, compared with other wall regions. No statistically significant correlation was found between the WMIs and maximum AAA diameter, except for longitudinal mean strain, which decreased with the increasing diameter (rho = −.42, p  < .010). Conclusion: Characterisation of wall kinematics by 4D ultrasound based WMIs provides a new and independent criterion for the distinction of diseased tissue in the AAA sac and the less affected neck region. This is a promising step towards the establishment of new biomarkers to differentiate between the mechanical instability of the AAA and rupture risk.